Elevated Frequencies of Circulating Th22 Cell in Addition to Th17 Cell and Th17/Th1 Cell in Patients with Acute Coronary Syndrome - Zhang, Lei (Public Library of Science, 2013)
BACKGROUND: Atherosclerosis is a chronic inflammatory disease mediated by immune cells. Th22 cells are CD4(+) T cells that secret IL-22 but not IL-17 or IFN-γ and are implicated in the pathogenesis of inflammatory disease. The roles of Th22 cells in the pathophysiologic procedures of acute coronary syndrome (ACS) remain unclear. The purpose of this study is to investigate the profile of Th22, Th17 and Th17/Th1 cells in ACS patients, including unstable angina (UA) and acute myocardial infarction (AMI) patients. DESIGN AND METHODS: In this study, 26 AMI patients, 16 UA patients, 16 stable angina (SA) patients and 16 healthy controls were included. The frequencies of Th22, Th17 and Th17/Th1 cells in AMI, UA, SA patients and healthy controls were examined by flow cytometry. Plasma levels of IL-22, IL-17 and IFN-γ were measured by enzyme-linked immunosorbent assay (ELISA). RESULTS: Th22, Th17 and Th17/Th1 cells were significantly increased in AMI and UA patients compared with SA patients and healthy controls. Moreover, plasma IL-22 level was significantly elevated in AMI and UA patients. In addition, Th22 cells correlated positively with IL-22 as well as Th17 cells in AMI and UA patients. CONCLUSION: Our findings showed increased frequencies of both Th22 and Th17 cells in ACS patients, which suggest that Th22 and Th17 cells may play a potential role in plaque destabilization and the development of ACS.